2022
DOI: 10.3389/fpsyg.2022.872593
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Computational Thinking and Empowering Metacognitive Awareness in Stem Education

Abstract: Education digitization highly enthuses learners for deeper learning and developing thought processes in formulating problems and their solutions effectively in their real-life circumstances. Implementing computational thinking skills through programming in Malaysian primary and secondary school STEM curriculum create huge challenges, especially among STEM educators. This study highlights the integration of four major theories in developing the Metacognitive Empowerment by Computational Thinking (ME-CoT) learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
1
3
0
2
Order By: Relevance
“…This means that learning approaches must offer active, interactive learning that allows students to actively break down problems into smaller steps (decomposition) and recognize patterns in various contexts. These findings support cognitive ideas by allowing students to process information, and discover and apply their ideas (Markandan et al, 2022).…”
Section: Resultssupporting
confidence: 53%
“…This means that learning approaches must offer active, interactive learning that allows students to actively break down problems into smaller steps (decomposition) and recognize patterns in various contexts. These findings support cognitive ideas by allowing students to process information, and discover and apply their ideas (Markandan et al, 2022).…”
Section: Resultssupporting
confidence: 53%
“…Esto se debe no solo a la emergencia en la literatura de nuevos enfoques o posturas, sino la tendencia que ha experimentado en tiempos recientes la educación STEM con respecto a la integración de disciplinas, procesos y preocupaciones, que, si bien muchas no son nuevas, condicionan la manera en que se produce. Aspectos como el liderazgo educativo y su vínculo con el enfoque STEM (Hatisaru et al, 2023), el vínculo entre niveles educativos y las implicaciones de la selección temprana de los programas STEM (Dixon et al, 2020), la gamificación y el uso innovador de dispositivos electrónicos (Chu et al, 2021;Hu et al, 2023), la motivación por el aprendizaje y el logro de los objetivos educativos (Arievitch, 2020;Markandan et al, 2022), así como la preparación docente y su compromiso con el mejoramiento de la educación STEM (Çiftçi y Topçu, 2022;Yang et al, 2021).…”
Section: Valoración Final De Los Resultadosunclassified
“…When students complete AI projects using the AI knowledge and technique they have, their inner potential and interest in learning are enhanced through the process of project prototype showcasing and competitor interaction [15]. Markandan et al [20] also found that CBL is being implemented correctly, which could enhance students' knowledge/technique sharing and transformation, and CBL could also raise their high-level cognitive technique, learning outcome, collaborating ability, and communication ability.…”
Section: Theoretical Knowledge Information Technology Practical and C...mentioning
confidence: 99%